Polypharmacy and Bleeding Outcomes After Percutaneous Coronary Intervention - Tada, Takeshi; Kimura, Takeshi; Morimoto, Takeshi; Kadota, Kazushige; Ishii, Katsuhisa; Onodera, Tomoya; Domei, Takenori; Sakai, Hiroshi; Inada, Tsukasa; Natsuaki, Masahiro; Furukawa, Yutaka; Shirotani, Manabu; et al. (Circulation Journal, 2024)
Background: Polypharmacy was reported to be associated with major bleeding in various populations. However, there are no data on polypharmacy and its association with bleeding in patients undergoing percutaneous coronary intervention (PCI).Methods and Results: Among 12,291 patients in the CREDO-Kyoto PCI Registry Cohort-3, we evaluated the number of medications at discharge and compared major bleeding, defined as Bleeding Academic Research Consortium Type 3 or 5 bleeding, across tertiles (T1–3) of the number of medications. The median number of medications was 6, and 88.0% of patients were on ≥5 medications. The cumulative 5-year incidence of major bleeding increased incrementally with increasing number of medications (T1 [≤5 medications] 12.5%, T2 [6–7] 16.5%, and T3 [≥8] 20.4%; log-rank P<0.001). After adjusting for confounders, the risks for major bleeding of T2 (hazard ratio [HR] 1.21; 95% confidence interval [CI] 1.08–1.36; P=0.001) and T3 (HR 1.27; 95% CI 1.12–1.45; P<0.001) relative to T1 remained significant. The adjusted risks of T2 and T3 relative to T1 were not significant for a composite of myocardial infarction or ischemic stroke (HR 0.95 [95% CI 0.83–1.09; P=0.47] and HR 1.06 [95% CI 0.91–1.23; P=0.48], respectively).Conclusions: In a real-world population of patients undergoing PCI, approximately 90% were on ≥5 medications. Increasing number of medications was associated with a higher adjusted risk for major bleeding, but not ischemic events.